Seedless fruit pummelo induced by Gamma Ray irradiation: Fruit morphological characters and stability evaluation - BAIQ DINA MARIANA; HIDAYATUL ARISAH; YENNI YENNI; MARRY SELVAWAJAYANTI (Biodiversitas Journal of Biological Diversity, 2018)
Mariana BD, Arisah H, Yenni, Selvawajayanti M. 2018. Seedless fruit pummelo induced by Gamma Ray irradiation: Fruit morphological characters and stability evaluation. Biodiversitas 19: 706-711. Pummelo is one of native citrus crops found in South East Asia including Indonesia. It is well known due to its big size and distinct taste compared to other citrus fruits. However, it contains many seeds, which may reduce the market demand and customer preferences. Therefore, the objective of this study was to generate seedless citrus by mutation techniques using gamma-ray radiation. The mutant induction of Pamelo Nambangan using gamma-ray radiation was conducted in 2003 using bud wood as plant materials. The bud wood was then irradiated with the dosage of 20, 40, and 60 Gy. The buds then grafted to Japansche Citroen rootstocks and maintained properly until the fruits could be observed. After three years of selection based on performance and fruit evaluation on MV2 generation, a mutant plant derived from 20 Gy irradiation treatments were obtained with improved character on the number of seeds. Pamelo Nambangan has more than 40 seeds/fruit and the mutant has less than 10 seeds/fruit on average. In the seedless mutant, it was observed that the mutant has embryo sac abortion leading to seedless fruit and low pollen viability (7.7%). The mutant has been released in 2016 as a new seedless pummelo variety under the name of ‘Pamindo Agrihorti’.